2018
DOI: 10.7717/peerj.5567
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine and microRNA levels during different periods of paradoxical sleep deprivation and sleep recovery in rats

Abstract: BackgroundSleep has a fundamental role in the regulation of homeostasis. The aim of this study was to assess the effect of different periods of paradoxical sleep deprivation (PSD) and recovery on serum levels of cytokines and miRNAs related to inflammatory responses.MethodsMale Wistar rats were submitted to a PSD of 24, 96, or 192 h, or of 192 h followed by 20 days of recovery (192 h PSD+R). The concentrations of corticosterone, cytokines (IL-6, TNF, IL-10, Adiponectin) and miRNAs (miR-146a, miR-155, miR-223, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 44 publications
6
9
0
Order By: Relevance
“…However, another study also comparing the effects of the single and multiple platforms methods, applied during 4 days, on the HPA axis activity of male rats showed that both protocols caused an increased secretion of corticosterone and ACTH, and confirmed that this effect was stronger in the single platform paradigm [138]. The stressful aspect of the multiple platforms apparatus was further highlighted in several other studies showing that 18 h to 21 days of REM-sleep suppression induced an increase in corticosterone and/or ACTH in male rats [139][140][141][142][143][144][145][146][147][148] and mice [149,150]. Other related methods using two small platforms or a 'grid over water' have been shown to also induce an increase in corticosterone in male mice after 2 and 3 days, respectively, [151,152].…”
Section: Do Sleep-deprivation Procedures In Rodentssupporting
confidence: 57%
“…However, another study also comparing the effects of the single and multiple platforms methods, applied during 4 days, on the HPA axis activity of male rats showed that both protocols caused an increased secretion of corticosterone and ACTH, and confirmed that this effect was stronger in the single platform paradigm [138]. The stressful aspect of the multiple platforms apparatus was further highlighted in several other studies showing that 18 h to 21 days of REM-sleep suppression induced an increase in corticosterone and/or ACTH in male rats [139][140][141][142][143][144][145][146][147][148] and mice [149,150]. Other related methods using two small platforms or a 'grid over water' have been shown to also induce an increase in corticosterone in male mice after 2 and 3 days, respectively, [151,152].…”
Section: Do Sleep-deprivation Procedures In Rodentssupporting
confidence: 57%
“…The levels of corticosterone in short-term sleep deprived mice exhibited a mild reduction; these results were consistent with those described in previous studies (Brianza-Padilla et al, 2018). The corticosterone levels of successively sleep-deprived mice has also been reported to increase significantly (Gonzalez-Castañeda et al, 2016; Brianza-Padilla et al, 2018). We also found that the ABR wave I amplitude was temporarily elevated following SD.…”
Section: Discussionsupporting
confidence: 93%
“…Many studies in rats support the notion that sleep alterations induce neuroinflammation. Depending on its duration, sleep deprivation can produce multiple physiological effects, including increased plasma corticosterone levels [80][81][82]. This suggests that paradoxical sleep deprivation (PSD) induces a stress response [83] as well as alterations in inflammatory markers, including IL-1β, IL-6, IL-17, and TNF-α [81,84,85], thus contributing to the neuroinflammatory process at the central level [86,87].…”
Section: Animal Studiesmentioning
confidence: 99%